Mechanical characterization of phase-changed single-layer MoS2 sheets. (28th February 2019) - Jung, Jaehyuck; Bark, Hunyoung; Byun, Doyoung; Lee, Changgu; Cho, Dae-Hyun
Abstract: Phase transitions in 2D materials, such as MoS2, result in drastic changes in the physical properties of the material. A change in the phase of MoS2 from 2H to 1T transforms it from a semiconductor to conductor, thus broadening its potential applications in electronics. The structural transformation associated with the phase change may significantly affect the mechanical properties. Here we statistically characterized the elastic modulus and fracture strength of phase-changed single-layer MoS2 sheets using the atomic force microscopy (AFM) nanoindentation technique. MoS2 sheets were subjected to lithium intercalation, which transformed them from the 2H phase to the 1T phase. The transformed sheets were again annealed to make a partially phase-changed sample. The elastic modulus and fracture strength of 1T phase MoS2 were about 50% lower than those of 2H phase MoS2 . Annealing of the 1T phase MoS2 sheet resulted in a good recovery of the mechanical properties, up to 90% of those of the original 2H phase MoS2 . This result was attributed to a mixture of phases in the annealed product, and the ratio of the phases was evaluated spectroscopically. Interestingly, while the fracture strengths differed for the three phases, their average fracture strains were quite similar, suggesting that the overall structure of the material maintained its integrity during the phase transition process.